Comfort and Conflict in Neonatal End-of-Life Care: A Mixed-Methods Study - Danielle Zamalin; Rachel Reed; Robert Green; Matthew J Drago (American Journal of Hospice and Palliative Medicine®, 2026)
Objective To evaluate neonatal providers’ comfort with end-of-life care (EOLC) and perceived palliative care (PC) resources using a two-domain analytic framework. Study Design Two-site, mixed-methods survey of nurses, neonatologists, pediatric hospitalists, advanced practice providers, and trainees in a Level III and Level IV NICU. Items were grouped into two domains: (1) comfort with participation in EOLC and (2) perceived PC resources and support. Multivariable hierarchical linear regression identified independent predictors of each domain, and free-text responses underwent inductive thematic analysis. Results Eighty-three clinicians responded. EOLC experience ( P < 0.001) and prior EOLC training ( P = 0.037) predicted higher comfort, whereas trainee status predicted lower comfort ( P = 0.012) (R 2 = 0.353). For perceived PC resources, provider role and NICU site were associated with higher scores (R 2 = 0.130). Qualitative themes highlighted competency gaps, personal and interpersonal conflicts, variable team culture, and structural constraints. Conclusions Provider comfort in neonatal EOLC reflects experiential, educational, and system-level factors. Interventions must combine training with cultural and structural investment.